1999
DOI: 10.1093/oxfordjournals.pcp.a029522
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast NADH Dehydrogenase from Pisum sativum: Characterization of its Activity and Cloning of ndhK Gene

Abstract: The pea chloroplast ndhK gene coding for a component of a NADH-plastoquinone oxidoreductase has been cloned and sequenced. This gene codes for a polypeptide of 227 amino acids and a predicted molecular mass of 25,495 Da which belongs to the family of the 20 kDa PSST subunit of the bovine mitochondrial complex I. A fragment of this gene has been overexpressed in Escherichia coli, and antibodies against the expressed polypeptide recognize a protein of the predicted molecular mass from pea thylakoid membranes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Similar results were obtained with the semipurified Ndh complex isolated by anion exchange followed by gel filtration, or by sucrose gradient combined with BN/PAGE (data not shown). Our results confirm some previously reported results [2–7], but disagree with other reports [8,9], and suggest that the 1000‐kDa Ndh complex described by these groups was actually a dimeric form. The observation that the molecular mass of the Ndh complex monomer is similar in both MS and BS chloroplast types led us to hypothesize that the architecture of the Ndh complex in other plastid types is similar.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar results were obtained with the semipurified Ndh complex isolated by anion exchange followed by gel filtration, or by sucrose gradient combined with BN/PAGE (data not shown). Our results confirm some previously reported results [2–7], but disagree with other reports [8,9], and suggest that the 1000‐kDa Ndh complex described by these groups was actually a dimeric form. The observation that the molecular mass of the Ndh complex monomer is similar in both MS and BS chloroplast types led us to hypothesize that the architecture of the Ndh complex in other plastid types is similar.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports regarding the molecular mass of the Ndh complex are ambiguous. While some groups reported that the molecular mass of this complex is 550-580 kDa [2][3][4][5][6][7], other groups have reported detection of the Ndh complex with a molecular mass between 800 and 1000 kDa [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Strict conclusions on the identity of the enzyme(s) involved cannot, however, be drawn solely on the basis of the oxidized reductant, as the substrate specificity of these enzymes is still a matter of controversy, and in some cases, the enzymes have been reported to use both NADH and NADPH (Corneille et al. , 1998; Elortza et al. , 1999; Funk et al.…”
Section: Discussionmentioning
confidence: 99%
“…PGR5 is expressed in both mesophyll cells and BSS of maize (Takabayashi et al 2005). The second pathway is the electron transfer to PQ via an NADPH-PQ reductase (NDH), which is highly homologous to complex I of bacteria and mitochondria Corneille et al 1998;Sazanov et al 1998;Elortza et al 1999). This pathway has been shown to be functional in cyanobacteria and plants (Mi et al 1995;Mano et al 1995Mano et al , 1997Shikanai et al 1998;Teicher and Scheller 1998;Joët et al 2002).…”
Section: Introductionmentioning
confidence: 99%